2010
DOI: 10.1242/jcs.064238
|View full text |Cite
|
Sign up to set email alerts
|

F-actin-binding protein drebrin regulates CXCR4 recruitment to the immune synapse

Abstract: SummaryThe adaptive immune response depends on the interaction of T cells and antigen-presenting cells at the immune synapse. Formation of the immune synapse and the subsequent T-cell activation are highly dependent on the actin cytoskeleton. In this work, we describe that T cells express drebrin, a neuronal actin-binding protein. Drebrin colocalizes with the chemokine receptor CXCR4 and F-actin at the peripheral supramolecular activation cluster in the immune synapse. Drebrin interacts with the cytoplasmic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 71 publications
6
48
0
Order By: Relevance
“…On the basis of the intracellular localization of DBN-1 and on a tentative functional comparison with its relatives, DBN-1 could furthermore modulate the plasticity and function of postsynaptic sites of neuromuscular junctions, analogous to mAbp1 and drebrin, which are known as essential players in both neurological [43][44][45]28 and immunological 30,29 synapses. In addition, DBN-1 may be involved in vesicle transport, similar to yeast and mammalian Abp1 homologues, which are well-described key regulators of receptor-mediated endocytosis, vesicle trafficking and endocytic structure disassembly [46][47][48][49]32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the intracellular localization of DBN-1 and on a tentative functional comparison with its relatives, DBN-1 could furthermore modulate the plasticity and function of postsynaptic sites of neuromuscular junctions, analogous to mAbp1 and drebrin, which are known as essential players in both neurological [43][44][45]28 and immunological 30,29 synapses. In addition, DBN-1 may be involved in vesicle transport, similar to yeast and mammalian Abp1 homologues, which are well-described key regulators of receptor-mediated endocytosis, vesicle trafficking and endocytic structure disassembly [46][47][48][49]32 .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, twinfilin binds to actin monomers and inhibits actin polymerization 25,26 . While the players of the third class, drebrin 1 (DBN1) and drebrin-like protein (DBNL; also known as Abp1, SH3P7 and HIP-55) have been associated with the function of neurological and immunological synapses [27][28][29][30] , their role in the sarcomere was unknown. Notably, in C2C12 myoblasts, expression of drebrin is induced during differentiation and is essential for myotube formation 31 .…”
mentioning
confidence: 99%
“…To assess the functional consequences of the effect of clathrin silencing on the physiology of the T cells, we measured the secretion of IL-2. It has been shown that reducing actin polymerization at the IS, either by using drugs, or by depleting actin-binding proteins, alters the secretion of IL-2 Perez-Martinez et al, 2010). Clathrin reduction deregulates IL-2 secretion (supplementary material Fig.…”
Section: Clathrin Is Necessary For Actin Accumulation At the Immunolomentioning
confidence: 99%
“…Drebrin is known to stabilize actin filaments (33,34). We have reported that the N-terminal region of drebrin associates with the cytoplasmic region of CXCR4 in CD4 ϩ T cells by three different approaches: mass spectrometry, pulldown assays, and co-immunoprecipitation (35). Despite containing a N-terminal ADF-H (actin depolymerizing factor homology) domain, drebrin only binds to polymerized (F-) actin and has no severing activity (36).…”
mentioning
confidence: 99%
“…Moreover, drebrin regulates the recruitment of other actin-regulatory proteins such as myosin, gelsolin, and profilin through direct association with them (38,39). We previously showed that interaction between drebrin and CXCR4 occurs at the T lymphocyte membrane and this molecular association is enhanced during superantigen presentation at the immunological synapse (35). However, the role of drebrin and its association with CXCR4 in controlling the cytoskeletal reorganization triggered by HIV-1 infection has not been previously described.…”
mentioning
confidence: 99%